Drugs under development for the treatment of functional dyspepsia and related disorders. (3rd October 2019) - Tack, Jan; Masuy, Imke; Van Den Houte, Karen; Wauters, Lucas; Schol, Jolien; Vanuytsel, Tim; Vandenberghe, Alain; Carbone, Florencia
ABSTRACT: Introduction : Functional dyspepsia (FD), defined as the presence of chronic functional symptoms originating from the gastroduodenal, is one of the most common functional gastrointestinal disorders. FD is subdivided into postprandial distress syndrome (PDS), with meal-related symptoms such as postprandial fullness and early satiation, and epigastric pain syndrome (EPS), with meal-unrelated symptoms such as epigastric pain or burning. Therapeutic options for FD are very limited, probably reflecting the complex pathophysiology which comprises disorders of gastric sensorimotor function as well as low-grade duodenal inflammation.Areas covered : This review summarizes recent and ongoing drug development for FD as identifiedExpert opinion : Proton pump inhibitors (PPIs) are the traditional first-line therapy while potassiumcompetitive acid blockers are being studied. Ongoing drug development focuses on gastric motility with prokinetics (dopamine-2 antagonists and 5-HT4 agonists) and fundus relaxant therapies (acotiamide, azapirones), and on sensitivity with peripherally (guanylate cyclase and cannabinoid agonists) and centrally acting neuromodulators. Drugs under development for gastroparesis may be efficacious in PDS. There are emerging data with pro-and antibiotics and with phytotherapeutic agents. Duodenal low-grade inflammation is a newly emerging target which may respond also to PPIs, histamine and leukotriene receptor blockers.